GERABAH GUA PAYUNG: JEJAK-JEJAK AUSTRONESIA DI KALIMANTAN BAGIAN SELATAN - Fajari, Nia Marniati Etie (Naditira Widya, 2010)
Pottery is one of the essensial indicator of human activity and subsistence in the past. Potteries excavated from Gua Payung come in various forms, made using advanced technology and decorated with attractive pattern. Analysis result on the morphological, technological and decoration aspect of the pottery provided information on pottery technology employed by human in Gua Payung, which in addition was used to interpret the existence of the Austronesian in Gua Payung. This interpretation concurs with linguistic data that Kalimantan is known as the crossroad for the Ausrtonesian migration in Southeast Asian Archipelago. This article discussed the analysis of Gua Payung pottery in regard to morphological, technological and decoration aspects.